2020
DOI: 10.1007/s40122-020-00213-0
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Magnetoencephalography Reveals Neurobiological Bridges Between Pain and Cognitive Impairment

Abstract: Introduction: Pain has been identified as a risk factor for cognitive dysfunction, which in turn affects pain perception. Although pain, cognitive dysfunction, and their interaction are clinically important, the neural mechanism connecting the two phenomena remains unclear. Methods: The resting-state brain activity of 38 participants was measured using magnetoencephalography before and after the patients underwent selective nerve root block (SNRB) for the treatment of their pain. We then assessed the extent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
0
5
0
1
Order By: Relevance
“…Pain is a common, unpleasant, subjective experience, and is one of the main reasons for visiting a healthcare facility, with approximately 40% of people suffering from different types of pain ( 37 ). Pain processing does not occur in a single brain region but is widely distributed in the cortical and subcortical network called the “pain matrix” ( 38 , 39 ), which influences cognitive functions, such as memory, attention, and executive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is a common, unpleasant, subjective experience, and is one of the main reasons for visiting a healthcare facility, with approximately 40% of people suffering from different types of pain ( 37 ). Pain processing does not occur in a single brain region but is widely distributed in the cortical and subcortical network called the “pain matrix” ( 38 , 39 ), which influences cognitive functions, such as memory, attention, and executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the amplitude in the low-frequency range of the fALFF to the total amplitude in the full frequency range reveals the relative effect of a specific low frequency over the entire frequency range ( 24 ). dfALFF reflects the dynamic changes in fALFF and reveals the characteristics of temporal and low-frequency oscillatory changes in the power of spontaneous brain activity ( 37 ). In this study, TA patients had increased dfALFF values in the right middle temporal, frontal middle, and right superior occipital gyri.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in demented patients, altered processing of pain and temperature have been described that contributes to differentiate clinical phenotypes [27]. Finally, by measuring the resting-state brain activity before and after selective nerve root block for the treatment of pain in demented patients, changes in MEG neural oscillations in various brain areas were found that represent the transient bridge between pain and cognitive dysfunction [28]. Overall, as a complex experience thought to emerge from the activity of multiple brain areas, pain affects cognitive functions such as attention, memory, and executive function [29], thereby adding value to the present finding of sensory cortex hyper-sensitivity in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state brain activity was recorded using MEG for 5 minutes, following the same protocol as that described in our previous studies. 11,16 The MEG system used was a 160-channel whole-head type (RICOH160-1; RICOH Co., Ltd., Tokyo, Japan), placed in a magnetically shielded room. During the scan, the participants were asked to remain relaxed in the supine position with their eyes closed.…”
Section: Meg Scanningmentioning
confidence: 99%